The Effect of Mental Health Training on Attitudes and Knowledge of Cadres in Early Detection of Mental Disorders in Tanjungsari Sub-district, Gunungkidul Regency - Nur Alifa Istiani; Adi Heru Sutomo; Mahar Agusno (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
ABSTRACTBackground: In developing countries, the proportion of undetected mental disorders is still high. This is due to the lack of time and skill of primary health care providers in early detection and therapy. Community empowerment through cadres plays an important role in improving the early detection of mental disorders. Attitudes and knowledge of cadres are influenced by several factors such as the level of formal education, employment status, economic status and the level of knowledge gained through training.Objectives: This study aimed to determine the effect of mental health training on the attitude and knowledge of cadres in the early detection of mental disorders.Methods: This study was a quasi-experimental research with a pre and posttest design. The population in this research was all (posyandu) volunteer cadres in the working area of the Community and Primary Health Care Center Hargosari, Tanjungsari, amounting to 45 people. The sampling technique used in this study was total sampling. The research instrument used was the questionnaire. Data analysis used the Wilcoxon test for comparison of scores (p<0.05).Results: The results of the mean value for pretest of knowledge = 13.44 and posttest = 17.38. Wilcoxon test showed there was a significant change in knowledge with the value p=0.0000 (<0.05). The results of the average value of pretest attitude = 36.71 and posttest = 45.20. Wilcoxon test showed there was a significant change in attitude with the value p = 0.0000 (<0.05).Conclusion: In conclusion, there was a significant influence by providing health training on the attitude and knowledge of cadres in the early detection of mental disorders in Tanjungsari District, Gunungkidul Regency.